2011
DOI: 10.3109/17549507.2011.549241
|View full text |Cite
|
Sign up to set email alerts
|

Lost in translation? Issues of content validity in interpreter-mediated aphasia assessments

Abstract: In many parts of the world, speech-language pathologists (SLPs) are frequently called upon to assess aphasia in bilingual speakers, or in speakers of languages of which they have little or no knowledge. One of the strategies that SLPs employ in these situations is to involve an interpreter in the assessment process. Three authentic interpreter-mediated aphasia assessments were analysed for the present study, which aimed to determine the degree to which the content validity of the individual tests was compromis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Factors that seemed to influence the team to function less effectively included the First Interpreter having separate conversations in Samoan with the FM during the language assessment and a poor seating arrangement. The findings of this study add to previous investigations that highlight the importance of more information sharing between interpreters and speech-language therapists including pre-and post-assessment briefings and the provision of information about the nature of the assessment process, the nature of communication disorders, and possible client errors (Kambanaros & Van Steenbrugge, 2004;Roger & Code, 2011).…”
Section: Discussionsupporting
confidence: 52%
“…Factors that seemed to influence the team to function less effectively included the First Interpreter having separate conversations in Samoan with the FM during the language assessment and a poor seating arrangement. The findings of this study add to previous investigations that highlight the importance of more information sharing between interpreters and speech-language therapists including pre-and post-assessment briefings and the provision of information about the nature of the assessment process, the nature of communication disorders, and possible client errors (Kambanaros & Van Steenbrugge, 2004;Roger & Code, 2011).…”
Section: Discussionsupporting
confidence: 52%
“…Although current evidence supports the provision of unilingual aphasia treatment in either the first (L1) or second (L2) languages [31], the myriad of languages spoken may mean that speech pathologists in Singapore may not be able to provide treatment in either of the client's languages. While it is recognized to be good practice to have interpreters in managing individuals from culturally and linguistically diverse backgrounds [32,33], interpreter-mediated sessions have been found to be prone to content validity issues [34].…”
Section: Introductionmentioning
confidence: 99%
“…Where language(s) spoken was reported, speech pathologist participants were mainly monolingual ( n = 220), compared with only 54 multilingual speech pathologist participants. Five studies reported that the interpreter participants involved were professional interpreters (Kambanaros and van Steenbrugge , Knoph , Koumanidi Knoph , Merlini and Favaron , Roger and Code ), while two survey studies mentioned family members being used as untrained interpreters (Hersh et al . , Roger et al .…”
Section: Resultsmentioning
confidence: 99%
“…() had reportedly interpreted for CALD adults with aphasia before. Additionally, the speech pathologist participants in Roger and Code () reported that working with interpreters was ‘not an uncommon event’ for them. Similarly, most studies did not report on previous training received by speech pathologist and interpreter participants on how to work together.…”
Section: Resultsmentioning
confidence: 99%